Zarządzanie wiedzą o e-klientach z wykorzystaniem systemu CRM - Jelonek, Dorota (The management of knowledge of e-customers with the use of the CRM system, 2005)
The aim of the paper is to show possibilities of using the CRM system in the management of knowledge of customers, who prefer doing shopping using the Internet network. In a situation, where the competitors have difficulties copying the best organizational or technological solutions, the knowledge of the customer can be an important factor behind the success in gaining competitive advantage in the marketplace. Knowledge is a unique resource and should therefore be subject to management procedures. Focusing attention on customers is a business philosophy, whose aim is the optimization of using their potential. It can considerably contribute to the success of a company in global, saturated and unstable markets. The tool assisting in the management of knowledge of customers are customer relation management systems
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 88-96